Analisa Proses Pembelajaran Berbasis Student Centered Learning, Problem Based Learning, Integrated, Community Based Learning, Electives, Systematic (SPICES) Terhadap Indeks Prestasi Mahasiswa Fakultas Kedokteran - Nadia Uluhiyah Muhammad; Sri Herlina; Marindra Firmansyah (Jurnal Kedokteran Komunitas, 2020)
Introduction : Improving the quality of medical education, especially in the learning system, will influence  the quality of medical students. With the need for public health and the development of  modern health technologies, a good curriculum is needed to support education in accordance with Indonesian Doctors Competency Standards (SKDI). The application of learning strategies with SPICES method (Student Centered Learning, Problem Based Learning, Integrative, Community Based Learning, Electives, Systematic) is an innovative educational strategy with the aim to support the student can learn independently and solving a problem. Therefore, research related to SPICES is needed to see the successful implementation of SPICES on Achievement Index among Faculty of Medicine students.Method: Observational analytic research design with cross-sectional approach was used. The research sample collection used non probability sampling technique, namely systematic sampling, the study sample was 183 medical students who were divided into 3 batches of 2016, 2017 and 2018. The data obtained were tested using the Spearman rho with Spearman rank correlation values.Result: The relationship between the implementation of each SPICES method (SCL, PBL, Integrated, CBL, Electives, Systematic) to student achievement index has P value <0.05 which means there is significance of each SPICES method with student achievement index. The correlation coefficient on the SCL method and overall SPICES shows a moderate correlation between 0.40 - 0.59, while the PBL, Integrated, CBL, Electives, Systematic methods show a low correlation between 0.20 - 0.39.Conclusion: The Student-Centered Learning Method and SPICES are moderately correlated to student academic achievement.Keywords: learning process, SPICES, Academic Achievement.